EFFECTS OF OPERATION PARAMETERS ON THE REMOVAL OF CARBAMAZEPINE AND NUTRIENTS IN A CERAMIC MEMBRANE BIOREACTOR - Chau, Dao Khanh (HUIT Journal of Science, 2024)
Pharmaceuticals and personal care products have raised significant concerns due to their widespread use and their potential impacts on wildlife and humans. Carbamazepine is the most frequently detected pharmaceutical residue among pharmaceutical and personal care products. However, the low removal efficiency of carbamazepine in wastewater treatment plants is due to its resistance to biodegradation at low concentrations. Membrane bioreactor (MBR) systems have recently attracted attention in municipal and industrial wastewater treatment because of their efficiency in separating pollutants. In this study, the main effects and interactions of three operating parameters, including hydraulic retention time - HRT (12–24 hours), dissolved oxygen concentration - DO (1.5–5.5 mg/L) and sludge retention time - SRT (5–15 days), in the removal of carbamazepine, chemical oxygen demand (COD), ammonia nitrogen and phosphorus using ceramic membranes was investigated by applying using a two-level full factorial design (FFD). The optimum dissolved oxygen concentration, hydraulic retention time and sludge retention time were 1.7 mg/L, 24 hours and 5 days, respectively. Research results show the applicability of MBR in wastewater treatment with high carbamazepine loading, along with the efficiency in removing nutrients.